Gestión administrativa en la hacienda Isabel del recinto los Balzares cantón puebloviejo - Salvatierra Gavilánez, Jorge Luis (2020)
This case study was carried out at the Isabel’s farm located in the Los Balzares area of the Puebloviejo canton, dedicated to the agricultural production of: rice, bananas and cocoa, it has an area of 40 hectares of land. In the property there are problematic situations that affect the administration, which is a technique in charge of planning, organizing, directing and controlling the resources of an institution. The objective of this investigation is to identify the different ethical and moral factors that cause problems within the administrative management. The methodology used is the qualitative method which helps to collect information based on the observation of natural behaviors where the interview for data collection was applied as a technique, obtaining as a result three main causes: inappropriate work strategies, inappropriate management of resources and deficit in inventory control systems causing delay in the proposed goals.